RECONSTRUCTION OF THE CENOZOIC STRUCTURAL HISTORY OF THE KUDAT PENINSULA, NORTHWEST SABAH: IMPLICATIONS TO THE EVOLUTION OF THE SOUTH CHINA SEA - MOHAMED ZAINUDDIN, NABILAH (2019)
Northern Borneo is a geologically complex region believed to be influenced by the rifting and opening of the South China Sea during the Oligocene to Middle Miocene. The Kudat Peninsula, which forms the northern tip of North Borneo, Northwest (NW) Sabah, exposed part of this complex geology. The Kudat Peninsula, which is underlain by Ophiolitic Basement, Crocker Formation, Kudat Formation, and a mélange unit, has undergone several episodes of deformation resulting in poor age control of the sediments and complex structural geology. This has resulted in the unresolved issue on the causality of oil seepage and the occurrence of mélange in the Kudat Peninsula. Geological and geophysical studies were conducted in the onshore and offshore of the Kudat Peninsula to evaluate the structural framework and the geological evolution of the Kudat Peninsula in relation to the opening of the South China Sea.